No effect of intensive training on plasma BDNF and cortisol concentrations in highly trained cyclists - Piacentini, M. F.; Witard, O. C.; Tonoli, C.; Guidotti, F.; Jackman, S. R.; Kies, A. K.; Jeukendrup, A. E.; Tipton, K. D.; Meeusen, R. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Short-term overload periods are frequently included in training programs in order to increase performance. Psychological mood state often responds rapidly to periods of increased training load and is therefore used as an early warning signal of nonfunctional overreaching (Meeusen et al. 2013). Recently, the role of brain derived neurotrophic factor (BDNF) in stress related mood disorders has been acknowledged (Duman and Monteggia 2006). Therefore, the purpose of the present study was to evaluate the effects of intensive training and recovery training on baseline plasma cortisol and BDNF concentrations and mood disturbances. Materials and methods: Eight trained cyclists (VO2max 64.2±6.5 ml/kg/min) performed 1 week of normal (NT), 1 week of overload (INT) and 1 week of recovery training (REC). Fasted blood samples were collected on day 7 of each training week and were analyzed for BDNF and cortisol. A 24 item Profile Of Mood State questionnaire was administered on day 7 of each week and global mood (GM) was calculated. A repeated measures ANOVA and a Pearson correlation test were used to verify differences due to training and the strength of the relationships between dependent variables in relation to training week. Results: Baseline cortisol (153±16 ng/ml NT, 130±11 ng/ml INT, 150±14 ng/ml REC) and BDNF (484±122 pg/ml NT, 488±122 pg/ml INT, 383±56 pg/ml REC) concentrations were not different between training conditions. GM increased significantly (21%) during INT and remained elevated during REC (7%) compared with NOR. Cortisol concentrations and GM were significantly correlated in NT (r=0.766) and RT (r=0.833). Discussion: These results confirm that changes in psychological parameters precede changes in commonly used biochemical markers and cortisol does not seem to be a useful measurement in monitoring athletes (Meeusen et al. 2013). BDNF has been related to stress induced mood disorders. Both acute and chronic stress paradigms decrease the expression of BDNF in the hippocampus probably caused by the increase in cortisol levels (Duman and Monteggia 2006) and exercise normally can counteract this downregulation. However, no correlation between cortisol, BDNF and GM was found during INT. It is likely that the INT followed immediately by REC prevented dysregulation of both BDNF and cortisol. Funding received from DSM Food Specialties, Delft, The Netherlands.